Epidemiology, Diagnosis and Preventive Measures of Zika Virus Infection: A Review Update (Bangladesh Journal of Infectious Diseases, 2017)
The relation between ZIKV infection during pregnancy and microcephaly in neonate has been established by the Brazillian Ministry of Health. Therefore, more attention regarding control of Aedes mosquito is required. Since it transmits this disease, which has more disastrous consequences than dengue viral infection. Potentially effective methods of prevention that are focused on reducing infections among pregnant women include avoiding unnecessary travel to areas of ongoing Zika virus transmission, avoiding unprotected sexual contact with partners who are at risk for Zika virus infection. According to Institute of Epidemiology Disease Control and Reseaech (IEDCR) there is nothing to panic at this moment for Bangladesh, but they stressed on mosquito control, which is the only tool to prevent and fight off Zika virus. They however, could not mention how the virus came to Bangladesh. May be somebody brought it while travelling. There is good survillence and testing system to detect the disease in Bangladesh.Bangladesh Journal of Infectious Diseases 2016;3(1):17-23